Towards a fusion of pedagogy and andragogy: a paradigm shift from malcolm knowles’ andragogical principles (2006)
This paper critically examines Malcolm Knowles’ andragogical principles as the basis for the learning process of adults. Knowles’ contention that the learning processes and principles of children (pedagogy) must be completely, different from that of the adults (andragogy) was vehemently disputed by some scholars based on the fact that humanistic psychology, upon which andragogy is rooted, assumes the problem of definition. Humanistic psychology does not make Knowles distinction between adults and children distinct enough. Instead, it applies its principles to all humans in spite of age. In essence, the four well-known features of adults (self directedness, rich experience, specific learning needs, and applied learning base) can all be applied in different ways to children. These submissions made Knowles to moderate his position regarding the differences between adult and younger learners. What he once strongly held on to as exclusive unique characteristics of adults, he later acknowledged as innate tendencies in all beings. Based on these contentions, this paper concludes that there is the need for a fusion between pedagogical and andragogical principles of learning which allows a bridge between the two methods of learning irrespective of the age of the learners.